The representation of classism in Joker (2019) - Khalfani, Muhammad Faisal Rayhan; Nafisah, Nia (Passage: Journal of English Language and Literature, 2025)
This research aims to understand the impact of classism on society. This research analyzes the people of Gotham and does not focus solely on the main character. Employing Marxist classism theory as the framework of the analysis and using Bordwell and Thompson’s (2008) formal system analysis to examine the narrative structure and film style, it revealed three findings. The first is that classism benefits the higher social class and neglects the lower social class. The second is that classism also creates a negative sentiment toward the lower social class and pictures the higher social class as good people. The third is that classism creates social discrimination and it creates Joker as a symbol of rebellion that creates chaos in Gotham City.